Double Standard dan “Open Minded”: Stigma Terhadap Social Justice Warrior pada Isu Feminisme di Twitter - Sari, Nur Amelia; Idrus, Nurul Ilmi (Universitas Muslim Maros, 2023)
Social Justice Warrior (SJW) is a pejorative term for someone who espouses progressivist views, such as civil affairs, multiculturalism, identity politics, and feminism. The accusation that someone is a SJW implies that they are seeking self-justification rather than truly believing in their views and are pretending to join in the debate. This creates a stigma against SJWs. Previous studies on stigma have focused more on sexual orientation and on people with certain diseases. This article will focus more on SJW on the issue of feminism. This qualitative research was conducted virtually examining stigma toward SJW in Twitter. It involves ten informants, consisting of a male and nine female informants whose age ranges between 20 and 33 years old. Data was collected using in-depth interview and observation. The study shows that SJW are stigmatized because the way they deliver their opinions that are considered to demean others, they have liberal thought, they equalise feminists as women who hate men and controversial opinions. There are two form of stigma to label SJW on Twitter, namely “open minded” and “double standard” insinuations. It turns out that stigma is impacted on SJW itself, which consist of being a victim of doxing, verbal abuse, and receiving blasphemy.